Hepatic resection after neoadjuvant chemotherapy for patients with liver metastases from colorectal cancer: need for cautious planning - Kim, Young Il (Ann Surg Treat Res, 2019)
PURPOSE: Current neoadjuvant chemotherapy (NAC) may enable therapies such as surgical resection and local ablation of metastases in patients with colorectal liver metastasis (CLM). We evaluated outcomes in CLM patients who underwent resection and/or local treatment after NAC and identified prognostic factors for oncologic outcomes. METHODS: Patients who received NAC followed by resection and/or local treatment of hepatic metastasis from 2013 to 2015 were included. Treatment and tumor-related variables were tabulated. Recurrence-free survival (RFS) and overall survival (OS) were analyzed using the Kaplan-Meier method. Cox regression analysis was used to identify factors associated with RFS and OS. RESULTS: Sixty-eight patients received NAC followed by resection and/or local treatment of hepatic metastases. Targeted therapy was administered in 50% of the patients. RFS was 35.8% at 1 year and 19.4% at 2 years postoperatively. OS was 95.6% at 1 year and 88.2% at 2 years postoperatively. In the multivariable analysis, R1 resection margin (hazard ratio [HR], 3.95; P = 0.008) of the liver metastases and ypN1/ypN2 (HR, 2.356 and 1.983, respectively; P = 0.041) were associated with poor RFS. Both factors were also significantly related to OS. CONCLUSION: Resection margin of the metastatic tumor and ypN status are the only relevant factors for RFS and OS in CLM patients treated with NAC. Despite early and high rates of recurrence, CLM patients treated with NAC who undergo resection and/or local treatment have acceptable OS. Multidisciplinary review of candidates for surgery and cautious planning are crucial for achieving optimal outcomes.